Impact of artificial plaque composition on drug transport. Issue 6 (9th April 2013) - Guo, Ji; Saylor, David M.; Glaser, Ethan P.; Patwardhan, Dinesh V.
Abstract Drug‐eluting stent (DES) implantation is a common treatment for atherosclerosis. The safety and efficacy of these devices will depend on the uptake and distribution of drug into the vessel wall. It is established that the composition of atherosclerotic vessels can vary dramatically with patients' age and gender. However, studies focused on elucidating and quantifying the impact of these variations on important drug transport properties, such as diffusion (D) and partition (k) coefficients, are limited. We have developed an improved tissue mimic or artificial plaque to probe the effect of varying concentrations of plaque constituents on drug transport in vitro. Based on these artificial plaques, we have quantified the impact of gelatin (hydrolyzed collagen) and lipid (cholesterol) concentration on D and k using two model drugs, tetracycline and fluvastatin. We found that for tetracycline, increasing the collagen concentration from 0.025 to 0.100 (w/w) resulted in a fivefold decrease in diffusivity, whereas there was no discernible impact on solubility. Increasing the lipid concentration up to 0.034 (w/w) resulted in only minor changes to transport properties of tetracycline. However, fluvastatin exhibited nearly a fivefold increase in k and 10‐fold decrease in D with increased lipid concentration. These results were in reasonable agreement with existing models and exhibited behavior consistent with previous observations on drugs commonly used in DES applications. These observations suggest that variations in the chemical characteristics of atherosclerotic plaque can significantly alter the release rate and distribution of drug following DES implantation. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:1905–1914, 2013